Negative regulation of endothelin signaling by SIX1 is required for proper maxillary development - Tavares, Andre L. P. (Development, 2017)
Jaw morphogenesis is a complex event mediated by inductive signals that establish and maintain the distinct developmental domains required for formation of hinged jaws, the defining feature of gnathostomes. The mandibular portion of pharyngeal arch 1 is patterned dorsally by Jagged-Notch signaling and ventrally by endothelin receptor A (EDNRA) signaling. Loss of EDNRA signaling disrupts normal ventral gene expression, the result of which is homeotic transformation of the mandible into a maxilla-like structure. However, loss of Jagged-Notch signaling does not result in significant changes in maxillary development. Here we show in mouse that the transcription factor SIX1 regulates dorsal arch development not only by inducing dorsal Jag1 expression but also by inhibiting endothelin 1 (Edn1) expression in the pharyngeal endoderm of the dorsal arch, thus preventing dorsal EDNRA signaling. In the absence of SIX1, but not JAG1, aberrant EDNRA signaling in the dorsal domain results in partial duplication of the mandible. Together, our results illustrate that SIX1 is the central mediator of dorsal mandibular arch identity, thus ensuring separation of bone development between the upper and lower jaws.